1982
DOI: 10.1056/nejm198206103062301
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Respiratory Viruses and Bacteria in the Etiology of Acute Otitis Media with Effusion

Abstract: We analyzed data from a 14-year longitudinal study of respiratory infections in young children to determine the relative importance of viral respiratory infection and nasopharyngeal colonization with Streptococcus pneumoniae and Haemophilus influenzae as factors influencing the occurrence of acute otitis media with effusion. The incidence of this disorder was increased in children with viral respiratory infections (average relative risk, 3.2; P less than 0.0001). Infection with respiratory syncytial virus, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
140
3
4

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(151 citation statements)
references
References 14 publications
4
140
3
4
Order By: Relevance
“…In the Western world, many studies have been performed concerning the nasopharyngeal carriage rates of potentially pathogenic bacteria in children with and without AOM or SOM (Box et al 1961, Kamme et al 1971, Branefors-Helander et al 1975, Schwartz et al 1979, Henderson et al 1982, Ingvarsson et al 1982a, Long et al 1983, Freijd et al 1984, Prellner et al 1984, Sørensen et al 1988, Faden et al 1991, Aniansson et al 1992. In most of these studies the nasopharyngeal colonization with potentially pathogenic bacteria have been shown to be associated with AOM, rAOM, and SOM while the quantitative aspects of colonization have shown more contradictory results maybe due to estimation difficulties.…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Western world, many studies have been performed concerning the nasopharyngeal carriage rates of potentially pathogenic bacteria in children with and without AOM or SOM (Box et al 1961, Kamme et al 1971, Branefors-Helander et al 1975, Schwartz et al 1979, Henderson et al 1982, Ingvarsson et al 1982a, Long et al 1983, Freijd et al 1984, Prellner et al 1984, Sørensen et al 1988, Faden et al 1991, Aniansson et al 1992. In most of these studies the nasopharyngeal colonization with potentially pathogenic bacteria have been shown to be associated with AOM, rAOM, and SOM while the quantitative aspects of colonization have shown more contradictory results maybe due to estimation difficulties.…”
Section: Aimsmentioning
confidence: 99%
“…The most frequent bacteria to be cultured from middle ear aspirations in children with AOM are Streptococcus pneumoniae (20-50%), Haemophilus influenzae (6-30%), Moraxella catarrhalis (0-10%), and group A streptococci (GAS) (0-5%) while Staphylococcus aureus and Chlamydia trachomatis have been found irregularly (Kamme et al 1971, Branefors-Helander et al 1975, Schwartz et al 1979, Chang et al 1982, Henderson et al .1982, Karma et al 1983, Long et al 1983, Giebink 1989, Arola et al 1990. Viruses have been found in coexistence with potentially pathogenic bacteria in 10 -30% of middle ear fluids and in the nasopharynx of 30 -55% of children with AOM (Henderson et al 1982, Arola et al 1990, Ruuskanen et al 1991.…”
Section: Aimsmentioning
confidence: 99%
“…These have included age (Sell, Turner & Federspiel, 1973), racial group (Turk, 1963), nursery attendance (Turk, 1963), institutional care (Turk, 1963;Mpaire, 1970), season of the year (Henderson et al 1982), presence of respiratory infection (Masters et al 1958), antibiotic therapy (Scheifele & Fussell, 1981), sampling techniques ) and laboratory methodology (Chapin & Doern, 1983). It is presumably differences in study design reflecting these many variables that has led to the diversity of findings.…”
Section: Introductionmentioning
confidence: 99%
“…Although this pathogen is associated with a variety of infections, it is also frequently isolated from the upper respiratory tract of healthy children with reported carrier rates of up to 60% [9]. The significance of nasopharyngeal colonization by NTHi is unclear, but colonization has been shown to be associated with an increased risk of developing acute otitis media and conjunctivitis in children attending day care centers [10].…”
mentioning
confidence: 99%